Comparison of baseline global gene expression profiles of prostate cancer cell lines LNCaP and DU145 - Khalid Ahmed; Zhannur Omarova; Alisalman Sheikh; Gulzhan Abuova; Kulsoom Ghias; Syed Hani Abidi (BMC Research Notes, 2024)
Abstract Introduction DU145 and LNCaP are classic prostate cancer cell lines. Characterizing their baseline transcriptomics profiles (without any intervention) can offer insights into baseline genetic features and oncogenic pathways that should be considered while interpreting findings after various experimental interventions such as exogenous gene transfection or drug treatment. Methods LNCaP and DU145 cell lines were cultured under normal conditions, followed by RNA extraction, cDNA conversion, library preparation, and RNA sequencing using the Illumina NovaSeq platform. The sequences were analyzed to identify differentially expressed genes (DEGs) and for gene ontology (GO) and pathway enrichment. Results A total of 3916 and 2301 genes were found to be differentially upregulated and downregulated between LNCaP and DU145 cell lines, respectively. The GO and pathway analysis of up-regulated DEGs indicated significant enrichment of genes involved in extracellular matrix organization and cell-substrate adhesion, while down-regulated genes are involved in epithelial cell migration, cell death regulation, and cell proliferation. Conclusion The results showed significant differences in baseline gene expression and cellular pathways that may account for the varying metastatic potentials between LNCaP and DU145 cell lines, which should be considered when interpreting findings after experimental interventions.